Code of Conduct Information System Using Simple Multi-Attribute Rating Technique (SMART) Method at SMK XYZ - Habib, Ahmad; Rozi, Dafid Ainur; Kusnanto, Geri (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
SMK XYZ is a vocational high school with approximately 2550 students with various majors and backgrounds, so there are many problems. For subscribers, each student gets a notebook on discipline and order; if a student commits a violation, it will be written by the discipline taught in the book. Furthermore, the counseling guidance teacher, together with the class teacher, conducts coaching; this activity is a manual system that has not been computerized. It hinders the performance of these teachers. From these problems, an order information system's analysis and design are carried out, which can facilitate and accelerate teachers in planning, directing, and monitoring. The SMART method's application to the discipline information system is based on the science of facts, which states a criterion with value; each weighted value can show and reflect comparisons between standards related to planning, direction, and supervision of students carried out by teachers. Subscription to violations using the discipline information system with the SMART method is carried out computerized, including determining sanctions and their actions to support the performance of teachers.